PENERAPAN METODE RESITASI UNTUK MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR - Welly Yuniarti; Johanes Sapri (DIADIK, 2023)
The purpose of this research (1) to describe how the application of the recitation method can increase the activity of Class X students High School DDM (2) To describe whether the application of the recitation method can improve student achievement in History of Islam subjects in Class X (3) To describe how the effectiveness of the application of the recitation method in improving student achievement in History of Islam subjects in class X High School DDM. The research design used is Classroom Action Research and Quasi-experimental. The research subjects were students of class X IPS1 Senior High School Dempo Darul Mutaqin Pagar Alam in the odd semester of the academic year 2021/2022 totaling 30 students. Through simple random sampling technique obtained quasi-experimental samples are class X IPS 2 totaling 28 students and X IPS3 totaling 28 students. The research instrument uses observation and tests. The research data were analyzed by descriptive statistics, average, percentage, and t test. The application of the Recitation Method can improve the learning activities of Class X Senior High School Dempo Darul Mutaqin students. Cycle I learning activities with an average of 50.9% active students and 49.1% inactive students. Cycle II with an average of 80% active students and 20% inactive students. This shows that the students' activities in learning Islamic Cultural History are in the very good category, which means that each indicator has been achieved. The application of the Recitation Method can improve student achievement in Class X MA Dempo Darul Mutaqin. Cycle I learning achievement with an average post-test of 66.33 with 18 students who completed and 12 students who did not complete. Cycle II with an average post-test of 83.33 with 28 students who completed and 2 students who did not complete. The percentage of students who completed reached 93.33%. From the results of the t-test calculation, the significance level is 5% and the degrees of freedom (dk) = 54, the average value of the experimental class is 80.35 and the average value of the control class is 69.54. obtained t arithmetic = 3.87 and t table = 2.00. Since tcount > ttable, it is significant. This means that the application of the recitation method is proven to be effective in increasing the Activity and Learning Achievement of Class X Students at Senior High School Dempo Darul Muttaqien Pagar Alam City